2007
DOI: 10.1353/pla.2007.0052
|View full text |Cite
|
Sign up to set email alerts
|

Portals for Undergraduate Subject Searching: Are They Worth It?

Abstract: In spring 2005, a task force of Oregon State University librarians investigated whether undergraduates would gravitate toward subject portals tentatively named "virtual college libraries." A literature review and Web site inventory shaped our definition of a virtual college library. A preliminary needs assessment consisting of an online survey, focus groups, and a usability study showed how students approach their information needs, what searching methods and technologies they typically use, and whether they u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…While searching once implied the physical exercise of sorting through objects in a collection, or words on a list, it is now the starting place for research, and increasingly it is understood as the only tangible method in research. Nichols and Mellinger () share what librarians observe anecdotally when working with students: “Millennials have a mental model of putting keywords into a search box” (481), and this leads them to underestimate the importance of browsing, monitoring, and being aware.…”
Section: Theorymentioning
confidence: 99%
“…While searching once implied the physical exercise of sorting through objects in a collection, or words on a list, it is now the starting place for research, and increasingly it is understood as the only tangible method in research. Nichols and Mellinger () share what librarians observe anecdotally when working with students: “Millennials have a mental model of putting keywords into a search box” (481), and this leads them to underestimate the importance of browsing, monitoring, and being aware.…”
Section: Theorymentioning
confidence: 99%
“…It was pleasing therefore to see an example of the contextualised information access, albeit serendipitous, of which I am sure Emily Walshe would approve in this issue of Portal. The preceding article (Nichols and Mellinger 2007), reporting a study of information behaviour of undergraduate students ('millenials' again) notes how this study, and others cited, showed that students repeated search strategies which had been successful in the past (even when they failed on this new occasion), avoided unfamiliar resources and different techniques, and generally relied on 'trusted sources', where trusted simply means used before.…”
Section: The Dark Side Of Documentation ?mentioning
confidence: 86%
“…Though the term 'Library Portal' appears new in this digital era, it has found that it's deeply rooted from print era when in traditional library users were using Card Catalogues to cater their information needs. In historical days Card Catalogue was acting as a 'Portal' or 'Single Stop' to find desired printed information [11]. Card catalogue was an effective tool for information discovery in the library.…”
Section: Development Of Library Portal In Print Eramentioning
confidence: 99%